Neuropathology of natural canid alphaherpesvirus 1 infection in dogs - Rissi, Daniel R. (Brazilian Journal of Veterinary Pathology, 2023)
The neuropathology of canid alphaherpesvirus 1 (CaHV-1) infection in dogs has been reported, but the importance of the cerebellar lesions in the routine diagnosis remains relatively understated in the veterinary literature. Here we characterize the neuropathology of natural CaHV-1 infection in 25 dogs. The disease affected predominantly male dogs (22 cases). Clinical signs in 15 cases varied and sudden death was reported in 10 cases. All dogs had the typical areas of necrosis and hemorrhage in multiple organs with eosinophilic intranuclear viral inclusions in epithelial and/or inflammatory cells in multiple organs in 21 cases. Cerebral swelling and reddening were reported in 3 cases. Neurohistologic changes consisted of mild lymphoplasmacytic meningoencephalitis with occasional vasculitis and widespread glial nodules. Rare intranuclear viral inclusions (4 cases) were observed in endothelial cells or inflammatory cells in glial nodules. Cerebellum was examined in 11 cases and had extensive segmental necrosis of Purkinje cell layer (8 cases) and granule neurons in the internal (9 cases) or external (2 cases) granular cell layer. Intranuclear viral inclusions were observed in 8 cases and occurred in necrotic granule neurons in the inner granular cell layer (7 cases), outer granular cell layer (2 cases), Purkinje neurons (1 case), or endothelial cells (1 case). Diagnostic confirmation in 23 cases was based on routine histology and fluorescent antibody testing for CaHV-1 on fresh or frozen tissue samples. A routine diagnosis was based solely on the visualization of intranuclear viral inclusions in 2 cases.